KESIAPAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) MENERAPKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK EMKM) - Sunan Amilia; Dewi Ayu Puspita; Hendrawan Santosa Putra (Universitas Jember, 2020)
The purpose of this study to analyze and discuss of optimism, innovativeness, and discomfort on the readiness of MSMEs to implement SAK EMKM. The sampling technique uses convenience sampling. Data is collected by using a questionnaire. This study used 74 MSME samples in Jember Regency. Data analysis methods in this study used descriptive statistics, data quality tests, classic assumption tests, and hypothesis testing consisting of multiple linear regression analysis methods, F test, t-test, and the coefficient of determination test. The results showed that optimism had a significant influence on the readiness of MSMEs to implement SAK EMKM. Innovativenes and discomfort do not have a significant effect on the readiness of MSMEs to implement SAK EMKM.Keywords: optimism, innovativeness, discomfort, SAK EMKM, readiness of MSMEs.